Current account composition and sustainability of external debt (I) - Gianpaolo Rossini; Paolo Zanghieri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2006)
If an economy runs a current account (CA) deficit and finances it via a corresponding net inflow of equity capital (belonging to foreign direct investment (FDI) or to portfolio investment) the external debt (ED) of the country does not change, i.e.: the CA deficit does not add to ED. This is no paradox and simply comes from the definition of CA deficit and external debt. Nonetheless, the implication of this is rather relevant since it points to different degrees of sustainability of CA deficits according to the way they are financed and to the composition of the CA itself. By the evaluation of the determinants of interest rates spreads of a country vis à vis US lending rates we assess the sustainability of CA deficits and we find that the extent of FDI net inflows (proxy of equity capital) allow emerging economies to sustain imbalances which are larger with respect to the case in which the CA deficit is financed by inflows of other more liquid assets. In other words the differential treatment of equity capital as a way of financing the CA, but not contributing to to the ED of a country, is no fiction and affects the solvency assessment of a country. This is a first result of a larger research on the effects of the composition of the CA on the solvency of an economy.
Keywords: 330